2008
DOI: 10.1038/nrn2294
|View full text |Cite
|
Sign up to set email alerts
|

Glucose neurotoxicity

Abstract: Neurons have a constantly high glucose demand, and unlike muscle cells they cannot accommodate episodic glucose uptake under the influence of insulin. Neuronal glucose uptake depends on the extracellular concentration of glucose, and cellular damage can ensue after persistent episodes of hyperglycaemia--a phenomenon referred to as glucose neurotoxicity. This article reviews the pathophysiological manifestation of raised glucose in neurons and how this can explain the major components of diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
391
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(413 citation statements)
references
References 128 publications
7
391
0
15
Order By: Relevance
“…Deficits in large fibre conduction velocity are generally considered to be among the earliest functional markers of glucose neurotoxicity, as they typically present before decreases in axonal diameter or structural disruption of the myelin in rodents 152 . In the absence of structural pathology, impaired nodal biophysical properties, such as ion flux and current densities, that might involve Schwann cell dysfunction have been implicated 152,153 .…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in large fibre conduction velocity are generally considered to be among the earliest functional markers of glucose neurotoxicity, as they typically present before decreases in axonal diameter or structural disruption of the myelin in rodents 152 . In the absence of structural pathology, impaired nodal biophysical properties, such as ion flux and current densities, that might involve Schwann cell dysfunction have been implicated 152,153 .…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 99%
“…In the absence of structural pathology, impaired nodal biophysical properties, such as ion flux and current densities, that might involve Schwann cell dysfunction have been implicated 152,153 . A study of rats with STZ-induced diabetes has shown that reduced motor conduction velocity is associated with upregulation of the Rho-Rho-kinase signalling pathway and consequent misexpression and aberrant distribution of the myelin sheath adhesion molecules p120 catenin and epithelial cadherin, which are crucial for normal myelin formation to allow rapid propagation of action potentials 154 .…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 99%
“…8 It has also been suggested that increased intracellular osmotic pressure via polyol (sorbitol) pathway would attribute to the changes in Tau and Ins levels observed in the diabetic brain. 24 The reasons underlying the differential changes of Tau in the striatum and hippocampus are unclear, but could be related to the fact that STZ-induced T1DM results in more severely perturbed glucose metabolism in the hippocampus than in the striatum. 25 Visual Cortex A number of clinical studies have investigated T1DM-related metabolic changes in the frontal 3,6 and occipital 5,26 cortex.…”
Section: Region-specific Metabolic Alterations At 4 Weeksmentioning
confidence: 99%
“…In aging, hyperglycemia is also associated with PD through damage to the central nervous system, a consequence of long-term exposure to glucose (Tomlinson and Gardiner 2008;Hu et al 2007). Epidemiologic studies suggest that previous type 2 diabetes is also a risk factor for developing PD (Mercer et al 2005).…”
Section: Brain Neurons and Parkinson's Diseasementioning
confidence: 99%